THE INFLUENCE OF SPATIAL DESIGN MODIFICATION ON BATU PAHAT LOW-COST PROPERTY INVESTMENT VALUE - Raji, Abdulazeez Umar (Journal of Technology Management and Business, 2018)
Spatial modification of terrace house in Malaysia is initiated by homeowners to satisfy their needs. Modification is more prevalent within the low income group occupying low-cost housing units due to their nature of their family size. The aim of this research is to develop a valuation model for low-cost terrace house spatial modification. This study explores the effects of post-occupancy changes and spatial modification in low-cost terrace housing. Additionally, it is to establish whether spatial modification being carried-out by homeowners has any price premium associated with their property value. The data was analyzed quantitatively using regression analysis. Each sample unit (homeowner) was provided with a questionnaire to obtain information on spatial modifications and key building related characteristics. The regression was done using both enter and stepwise methods. The findings indicate that the critical factors influencing residential property value of spatially modified low-cost terrace housing are Sale year (age), Number of bedrooms, Plot area, Gross floor area, Modified area, Extra-kitchen, Extra-bedroom, Extra-storage. Whilst, a price (value) premium on their current investment of 19.3%, 4.7% and 8.4% can be attained by adding extra-kitchen, bedroom and kitchen respectively. The results show that the variables accounted for R square = 86.6% of the variance in regression. Hence, the hedonic house value model is proposed to help homeowners in spatial modification appraisal. The strong recommendation of the study is that homeowners of low-cost terrace housing should clearly consider spatial modifications by prioritizing value enhancement objectives aimed at enhancing opportunities for social mobility.